Geophysical characterization of landslides in Serbia and Bosnia and Hercegovina - A GWB project - Urosevic, M.; Komatina, S.; Burazer, M.; Suto, K.; Arsenovic, S.; Milosevic, D.; Ziramov, Sasha; Coren, F. (2016)
Continuous, heavy rainfall commencing in May 2014 has resulted in extensive flooding in Serbia, Bosnia and Herzegovina (BiH). Thousands of landslides developed rapidly after several days of torrential rain. Shortly after a diverse group of geophysicists and geologists got together and set out a project to investigate these landslides. The main objective was to characterize and categorize landslides and provide results that could help devise an optimum mitigation program. Prediction of the reactivation potential of landslides was also of direct interest to the investigations. In the first phase of the project investigations included simultaneous acquisition of reflection, refraction, MASW and resistivity data along 17 profiles, distributed over six different localities. In addition, a mini 3D survey was successfully recorded along steep slope. These measurements were supported by sparse drilling, logging, coring, geotechnical analysis and the airborne laser scans. Very good agreement was achieved between different methods, despite vastly different geometry and composition of landslides. Joint analysis of resistivity images, reflection data, and P and S-velocity fields, obtained from refraction tomography and inversion of surface waves, provide new geological insights that are important for understanding the mechanism of a landslide. This will provide valuable input for a mitigation program.